Does banning price discrimination promote entry and increase welfare? A model of differentiated-product duopoly with asymmetric markets - Jorge, S.F. (2014)
In this paper we investigate the impact of firms’ pricing policies upon entry and welfare under duopoly price competition and product differentiation. We consider a model where an incumbent serves two distinct and independent geographical markets and an entrant may enter in one of the markets. Our results show that discriminatory pricing may be either more, less or equally favorable to entry than uniform pricing. The welfare effect of banning price discrimination is also ambiguous. However, the case for banning price discrimination is much weaker than under monopoly. Interestingly, discriminatory pricing may yield higher welfare even when entry occurs only under uniform pricing.